The “Transfiguration” Icon — the Main Image of the Solovetsky Monastery Cathedral: The Peculiaritiesand the Interpretation of the Iconographic Programme - Samoylova, Tatiana E. (Actual Problems of Theory and History of Art, 2017)
The Transfiguration icon, housed in the Moscow Kremlin museum, is the main icon of the Transfiguration cathedral of the Solovetsky Monastery. The icon was painted around 1558 by masters from Novgorod, bearing influence of the Moscow painting trends. The classical iconography of the Transfiguration in this icon is diversified with four more themes. The first one depicts two prophets carried by angels to the Mountain Tabor. The second presents the apostles headed by Christ going up and down the mountain. Тhe third is the parable of new and old wine. The fourth shows the Jewish people meeting Christ. The third and the fourth themes are quite unique. The Homily on Transfiguration by Ephrem the Syrian helps us decipher the iconographical design of this image. The sophistication and the refinement of the way the main ideas of the text are put into painting suggest that the content was elaborated by a person of theological and artistic mind. No doubt the iconic image was designed by Philipp, the Metropolitan, and it is a bright feature of Philipp, who at that period was the abbot of the Solovetsky Monastery. A very interesting person, an outstanding figure of that epoch, Philipp manifested himself as an apologist of the Old Testament wisdom which nourishes The Church as well as the New Testament.
Keywords: iconography of Transfiguration; icon; Solovetsky Monastery; iconographic program; Saint Philipp; the Metropolitan of Moscow Efrem Sirin